Clinic Management System for Hope Clinic Bukit Serdang - Chang Bing Hui; Mohd Najib Mohd Salleh (Applied Information Technology And Computer Science, 2021)
Clinic Management System is developed to support the clinic daily operation before this is done manually. This system will involve all the clinic operation starting from patient and doctor registration until patient reviewing. The important thing is it will become easier for the data record and retrieval. This system will be able to generate report regarding the clinic operation. For example, the number of patients per day and total disease per day. The target user for this system is staff of the clinic, doctor, patient, and admin management. The scope of this project includes mapping in appointment module, login/Register module, reviewing module, reporting module and notifying user. Waterfall approach is applied while developing this system. This will involve an iterative process to make this system is usable and easy to use by the user. The design for the system is using the System Development Life Cycle (SDLC) approach. The design will involve entity relationship diagram (ERD) and Data Flow Diagram (DFD) to show the logical flow for the system. For the implementation, Apache is used as a web server, MySQL as a database, PHP as a scripting language and browser. The main important while developing any system is to make the system usable.